2011
DOI: 10.1007/s00421-011-1928-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of power output on muscle coordination during rowing

Abstract: The present study was designed to quantify the effect of power output on muscle coordination during rowing. Surface electromyographic (EMG) activity of 23 muscles and mechanical variables were recorded in eight untrained subjects and seven experienced rowers. Each subject was asked to perform three 2-min constant-load exercises performed at 60, 90 and 120% of the mean power output over a maximal 2,000-m event (denoted as P60, P90, and P120, respectively). A decomposition algorithm (nonnegative matrix factoriza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 39 publications
4
34
0
Order By: Relevance
“…This is similar to the findings of Turpin et al (2011) for the rowing cycle were significant increase in EMG activation were found with increased power output, but at the same time the timing of activation and the shape of individual EMG patterns remained similar. On the contrary Schache et al (2013) found a change in muscle coordination from jogging (ankle plantar flexion muscles dominated) to sprinting (hip flexor and extensor muscles become more critical).…”
Section: Muscle Activationsupporting
confidence: 89%
See 1 more Smart Citation
“…This is similar to the findings of Turpin et al (2011) for the rowing cycle were significant increase in EMG activation were found with increased power output, but at the same time the timing of activation and the shape of individual EMG patterns remained similar. On the contrary Schache et al (2013) found a change in muscle coordination from jogging (ankle plantar flexion muscles dominated) to sprinting (hip flexor and extensor muscles become more critical).…”
Section: Muscle Activationsupporting
confidence: 89%
“…Similar muscle activation patterns, motor control strategies and muscle coordination were also reported during rowing. Turpin, Guével, Durand, and Hug (2011) found a significant increase in EMG activation with increased power output, but at the same time, no dramatic changes in the timing of activation or in the shape of individual EMG patterns. Guével et al (2011) found the shape of the EMG patterns to be very similar between 65-75% and 75-85% of maximal heart rate.…”
Section: Introductionmentioning
confidence: 73%
“…Our results also showed that the 3-min all-out test on the rowing ergometer provides moderate reliability. Turpin et al (2011) noted that significant differences exist in the force profile and muscle activities during submaximal and maximal rowing, between untrained participants and experienced rowers. Thus, we recruited reasonably experienced rowers into our study to reduce the effects of differences in personal skill levels.…”
Section: Discussionmentioning
confidence: 96%
“…The rowing cycle is divided into a drive phase (from the frontal to the rear movement reversal) and a recovery phase (from the rear reversal to the next frontal reversal) (Janshen et al 2009). Turpin et al (2011) found that most of the recorded 23 muscles involved, including both the upper and lower body muscle groups, were activated during the drive phase and relaxed during the recovery phase. Thus, alternation of the drive and recovery phases may provide a rest interval for the muscles, and delay the power output decline; thereby then producing an apparent increased WEP capacity.…”
Section: Discussionmentioning
confidence: 98%
“…As previously done with sEMG data recorded during cyclic activities (Hug et al, 2010Turpin et al, 2011), the Lee and Seung algorithm (2001) was used to perform the NMF. The residual Frobenius norm between the initial matrix and its decomposition was minimized by matrix factorization, given as:…”
Section: Processing Of Surface Electromyography Signalsmentioning
confidence: 99%